ASSESSMENT OF THE EFFECTIVENESS OF INDIVIDUAL BONE PLATES IN THE SURGICAL TREATMENT OF MANDIBULAR ANGLE FRACTURES - Matchanov Bobur Bakhtiyor o’g’li (Western European Studies, 2025)
Adequate immobilization of mandibular fragments is a key prerequisite for successful treatment of mandibular fractures. Fractures located in the angle region of the mandible present significant challenges for intraoral fixation due to the complex anatomical geometry, often requiring extensive bending of standard plates, which leads to increased operative time and reduction in plate strength. To address these limitations, an original design of an individualized incisal plate was developed for intraoral osteosynthesis in the mandibular angle region. A virtual stress–strain analysis of the mandible under physiological loading demonstrated the biomechanical advantages of the individualized plates compared with standard configuration plates. The plate consists of two fixing arms of different lengths connected by an intermediate segment, with geometry tailored to each patient’s mandibular anatomy. Plates were manufactured using high-precision milling technology (Roland MDX-540). Clinical application involved intraoral access, stepwise elevation of a mucoperiosteal flap, anatomical repositioning of fragments, and sequential fixation with intraosseous screws. The individualized plate enabled stable fixation with minimal tissue trauma and reduced operative time due to its anatomical congruence. Early postoperative rehabilitation was possible owing to the favorable distribution of functional loads. The use of patient-specific incisal plates represents an effective and minimally invasive method for treating fractures of the mandibular angle.
Keywords: mandibular angle fracture; individualized incisal plate; intraoral fixation